Adaptive NK Cell Therapy Modulated by Anti-PD-1 Antibody in Gastric Cancer Model - Shahrokh Abdolahi; Zeinab Ghazvinian; Samad Muhammadnejad; Mohammad Ahmadvand; Mohammad Ahmadvand; Hamid Asadzadeh Aghdaei; Somayeh Ebrahimi-Barough; Jafar Ai; Mohammad Reza Zali; Javad Verdi; Kaveh Baghaei; Kaveh Baghaei (Frontiers Media S.A., 2021)
Recently, adaptive NK cell therapy has become a promising treatment but has limited efficacy as a monotherapy. The identification of immune checkpoint inhibitor (ICI) molecules has opened a new horizon of immunotherapy. Herein, we aimed to demonstrate the cytotoxic effects of a polytherapy consisting of ex vivo expanded IL-2-activated NK cells combined with human anti-PD-1 antibody as an important checkpoint molecule in a xenograft gastric cancer mouse model. EBV-LCL cell is used as a feeder to promote NK cell proliferation with a purity of 93.4%. Mice (NOG, female, 6-8 weeks old) with xenograft gastric tumors were treated with PBS, ex vivo IL-2-activated NK cells, IL-2-activated NK cell along with human anti-PD-1 (Nivolumab), and IL-2-activated pretreated NK cells with anti-PD-1 antibody. The cytotoxicity of ex vivo expanded NK cells against MKN-45 cells was assessed by a lactate dehydrogenase (LDH) assay. Tumor volume was evaluated for morphometric properties, and tumor-infiltrating NK cells were assessed by immunohistochemistry (IHC) and quantified by flow cytometry. Pathologic responses were considered by H and E staining. Ex vivo LDH evaluation showed the cytotoxic potential of treated NK cells against gastric cancer cell line. We indicated that the adoptive transfer of ex vivo IL-2-activated NK cells combined with anti-PD-1 resulted in tumor growth inhibition in a xenograft gastric cancer model. Mitotic count was significantly decreased (*p < 0.05), and the tumor was associated with improved infiltration of NK cells in the NK-anti-PD-1 pretreated group (*p < 0.05). In conclusion, the combination approach of activated NK cells and anti-PD-1 therapy results in tumor growth inhibition, accompanied by tumor immune cell infiltration in the gastric tumor model.